The effects of dehydration before competition upon body compositions, leptin hormone and ghrelin hormone among elite wrestlers - Cicioglu, H. I.; Isik, O.; Yildirim, I.; Unveren, A.; Karagoz, S. (Biomedical Research, 2017)
The aim of the study was to determine the changes in body compositions and hydration levels before a competition among elite wrestlers and to demonstrate the difference among leptin and ghrelin hormone levels due to dehydration. Pre and post-test measurements were performed among the twenty-four voluntary wrestlers in before an international tournament. A personal information form that addressed pre-competition weight loss duration and demographic variables was administered to the participant wrestlers. Additionally, body compositions were analyzed using BIA (Bioelectric Impedance Analyzer), and with the help of specialists, 5 cc of blood was drawn from the forearm veins of the wrestlers. Sodium (Na+), Blood Urea Nitrogen (BUN), glucose, leptin and ghrelin levels were analyzed in the blood samples. The wrestlers' Plasma osmolarity (POsm) levels were calculated through Na+, BUN and glucose in a mathematical formula. The wrestlers who had POsm>290 mOsm/L constituted the weight loss group while the wrestlers who had POsm = 290 mOsm/L constituted the non-weight loss group. It was identified that all the body composition variables of weight loss group were different both in the pre-test and posttest. Furthermore, BUN, glucose, POsm and ghrelin hormone levels of the weight loss group were different whereas there were no differences in sodium and leptin levels. As a result, it was found that wrestlers who lost weight before a competition did it quickly; therefore, wrestlers who underwent significant changes in their body compositions demonstrated serious increases in POsm and ghrelin hormone levels.